Wanted DEAD/H or Alive: Helicases Winding Up in Cancers. - Cai, W.; Xiong Chen, Z.; Rane, G.; Satendra Singh, S.; Choo, Z.; Wang, C.; Yuan, Y.; Zea Tan, T.; Arfuso, Frank; Yap, C.; Pongor, L.; Yang, H.; et al. (Oxford University Press, 2017)
Cancer is one of the most studied areas of human biology over the past century. Despite having attracted much attention, hype, and investments, the search to find a cure for cancer remains an uphill battle. Recent discoveries that challenged the central dogma of molecular biology not only further increase the complexity but also demonstrate how various types of noncoding RNAs such as microRNA and long noncoding RNA, as well as their related processes such as RNA editing, are important in regulating gene expression. Parallel to this aspect, an increasing number of reports have focused on a family of proteins known as DEAD/H-box helicases involved in RNA metabolism, regulation of long and short noncoding RNAs, and novel roles as "editing helicases" and their association with cancers. This review summarizes recent findings on the roles of RNA helicases in various cancers, which are broadly classified into adult solid tumors, childhood solid tumors, leukemia, and cancer stem cells. The potential small molecule inhibitors of helicases and their therapeutic value are also discussed. In addition, analyzing next-generation sequencing data obtained from public portals and reviewing existing literature, we provide new insights on the potential of DEAD/H-box helicases to act as pharmacological drug targets in cancers.